Analysis of the Implementation of Physical Education Programs in Early Childhood - husnul, Husnul Khatimah; Juwita, Rani Puspa (JURNAL PENA PAUD, 2025)
Physical education plays an essential role in the development of gross motor skills in early childhood. Physical activity helps children improve gross motor skills and reduces the risk of health problems; therefore, physical education programs play a significant role in supporting their growth and development. This study aims to examine the impact of physical education programs on the gross motor development of 5 6-year-old children at Bunda Kandung Kindergarten. Using a descriptive qualitative approach, data were collected through semi-structured interviews and documentation. The research subjects were two informants: the principal and the classroom teacher. To ensure data validity, the researcher employed triangulation of sources. Data analysis was conducted using Miles and Huberman's model, which comprises three main stages: data reduction, data presentation, and conclusion. The results showed that the physical education program was not running optimally, as evidenced by low child participation, a limited variety of physical activities, and limited supporting facilities. These findings emphasize the need for a comprehensive evaluation and development of physical education programs to enhance their effectiveness in promoting gross motor development in early childhood.